Uji Stabilitas Gel Ekstrak Daun Mugwort (Artemisia vulgaris L.) dan Aktivitas Antibakteri Terhadap Staphylococcus aureus - Umi Nafisah; Purwaningsih Purwaningsih; Ansela Permata Sari (Journal of Pharmaceutical and Sciences, 2026)
Staphylococcus aureus is a gram-positive bacterium that can multiply in body tissues and cause disease. Treatment of infections caused by Staphylococcus aureus bacteria can be done with the use of antibacterial agents. One natural ingredient that contains active compounds with potential antibacterial properties is mugwort leaves (Artemisia vulgaris L.). This study aims to determine the antibacterial activity and physical stability of mugwort leaf extract gel against Staphylococcus aureus. The method used to test antibacterial activity in this study was disc diffusion, measuring the zone of inhibition formed around the paper disc. The concentrations of mugwort leaf extract gel tested and formulated were 5%, 7.5%, and 10%. The physical stability of the gel was tested using a cycling test, with observations before and after the test. The results showed that mugwort leaf extract has antibacterial activity against Staphylococcus aureus bacteria. The antibacterial activity test for the gel yielded results of 5% gel: 4.17 mm, 7.5%: 5.67 mm, and 10%: 8.17 mm. The physical stability test results showed that the gel was homogeneous, had good spreadability and pH, and had good physical stability.